Biocatalysis mechanism for p-fluoronitrobenzene degradation in the thermophilic bioelectrocatalysis system: Sequential combination of reduction and oxidation. (September 2016) - Wang, Yanfeng; Zhang, Xueqin; Feng, Huajun; Liang, Yuxiang; Shen, Dongsheng; Long, Yuyang; Zhou, Yuyang; Dai, Qizhou
Abstract: To verify the potentially synthetic anodic and cathodic biocatalysis mechanism in bioelectrocatalysis systems (BECSs), a single-chamber thermophilic bioelectrocatalysis system (R3) was operated under strictly anaerobic conditions using the biocathode donated dual-chamber (R1) and bioanode donated dual-chamber (R2) BECSs as controls. Direct bioelectrocatalytic oxidation was found to be infeasible while bioelectrocatalytic reduction was the dominant process for p -Fluoronitrobenzene ( p -FNB) removal, with p -FNB removal of 0.188 mM d −1 in R1 and 0.182 mM d −1 in R3. Cyclic voltammetry experiments confirmed that defluorination in the BECSs was an oxidative metabolic process catalyzed by bioanodes following the reductive reaction, which explained the 0.034 mM d −1 defluorination in R3, but negligible defluorination in controls. Taken together, these results revealed a sequentially combined reduction and oxidation mechanism in the thermophilic BECS for p -FNB removal. Moreover, the enrichment of Betaproteobacteria and uniquely selected Bacilli in R3 were probably functional populations for p -FNB degradation. Highlights: Bioanode biocatalytic defluorination occurred after bioelectrocatalytic reduction. p -FNB was removed by an integrated reduction and oxidation metabolism mechanism. Both the biocatalysis synthesizing bioanode and biocathode degraded p -FNB.